2019
DOI: 10.1096/fj.201902086r
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of microRNA‐874‐3p implicates in erectile dysfunction in diabetic rats by activating the Nupr1/Chop‐mediated pathway

Abstract: Diabetes is a global medical problem that causes many deaths every year.Complications caused by diabetes are serious and affect patients' quality of life.Diabetes mellitus erectile dysfunction (DMED) affects more than half of male diabetes patients. In this study, we determined the role of microRNA-874-3p (miR-874-3p) and nuclear protein-1 (Nupr1) in streptozocin-induced DMED rats. Control rats received equal amount of vehicle. These rats were also injected with lentiviral vector or agomir to silence or overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
(145 reference statements)
2
13
0
Order By: Relevance
“…Huang et al (2018) found that silencing circ_0000977 promoted the apoptosis of pancreatic ductal adenocarcinoma cells by stimulating miR-874-3p and inhibiting PLK1 expression. However, miR-874-3p has been confirmed to inhibit the apoptosis of brain tissue (Jiang et al, 2019;Xie et al, 2020) and cavernosal smooth muscle cells (Huo et al, 2020). The different roles of miR-874-3p may be related to cell state and type.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2018) found that silencing circ_0000977 promoted the apoptosis of pancreatic ductal adenocarcinoma cells by stimulating miR-874-3p and inhibiting PLK1 expression. However, miR-874-3p has been confirmed to inhibit the apoptosis of brain tissue (Jiang et al, 2019;Xie et al, 2020) and cavernosal smooth muscle cells (Huo et al, 2020). The different roles of miR-874-3p may be related to cell state and type.…”
Section: Discussionmentioning
confidence: 99%
“…Many pieces of evidence have shown that miRNAs have diagnostic and predictive value for DMED in mice ( Li et al, 2017 ; Cong et al, 2020 ; Huo et al, 2020 ). However, few correlational researches of DMED have been conducted on the human body.…”
Section: Resultsmentioning
confidence: 99%
“…The constructed ceRNA network predicted that both miR-874-3p and miR-339-5p significantly interacted with circ-ICAM1. Huo et al found that the expression of miR-874-3p in diabetic rats was significantly downregulated, which led to increased islet b cell apoptosis and diabetes-induced erectile dysfunction by targeting the inhibition of the nuclear protein 1 (Nupr1)-mediated pathway (62). It was also observed that miR-339-5p and miR-874-3p mediate high glucose-induced endothelial inflammation by targeting interleukin-1 receptorassociated kinase 1 (IRAK1) expression (63).…”
Section: Discussionmentioning
confidence: 99%